Long-term no-till: A major driver of fungal communities in dryland wheat cropping systems. - Dipak Sharma-Poudyal; Daniel Schlatter; Chuntao Yin; Scot Hulbert; Timothy Paulitz (PLoS ONE)
In the dryland Pacific Northwest wheat cropping systems, no-till is becoming more prevalent as a way to reduce soil erosion and fuel inputs. Tillage can have a profound effect on microbial communities and soilborne fungal pathogens, such as Rhizoctonia. We compared the fungal communities in long-term no-till (NT) plots adjacent to conventionally tilled (CT) plots, over three years at two locations in Washington state and one location in Idaho, US. We used pyrosequencing of the fungal ITS gene and identified 422 OTUs after rarefication. Fungal richness was higher in NT compared to CT, in two of the locations. Humicola nigrescens, Cryptococcus terreus, Cadophora spp. Hydnodontaceae spp., and Exophiala spp. were more abundant in NT, while species of Glarea, Coniochaetales, Mycosphaerella tassiana, Cryptococcus bhutanensis, Chaetomium perlucidum, and Ulocladium chartarum were more abundant in CT in most locations. Other abundant groups that did not show any trends were Fusarium, Mortierella, Penicillium, Aspergillus, and Macroventuria. Plant pathogens such as Rhizoctonia (Ceratobasidiaceae) were not abundant enough to see tillage differences, but Microdochium bolleyi, a weak root pathogen, was more abundant in NT. Our results suggest that NT fungi are better adapted at utilizing intact, decaying roots as a food source and may exist as root endophytes. CT fungi can utilize mature plant residues that are turned into the soil with tillage as pioneer colonizers, and then produce large numbers of conidia. But a larger proportion of the fungal community is not affected by tillage and may be niche generalists.